Chronic baroreflex activation effects on sympathetic nerve traffic, baroreflex function, and cardiac haemodynamics in heart failure: a proof‐of‐concept study. (28th July 2014) - Gronda, Edoardo; Seravalle, Gino; Brambilla, Gianmaria; Costantino, Giuseppe; Casini, Andrea; Alsheraei, Ali; Lovett, Eric G.; Mancia, Giuseppe; Grassi, Guido
<x xml:space="preserve">Abstract</x> Aims Heart failure (HF) pathophysiology is believed to be mediated by autonomic dysfunction, including chronic sympathoexcitation and diminished baroreflex sensitivity, which correlate with mortality risk. Baroreflex activation therapy (BAT) is a device‐based treatment providing chronic baroreflex activation through electrical stimulation of the carotid sinus. BAT chronically reduces sympathetic activity in resistant hypertension. The purpose of this investigation is to determine BAT effects in clinical HF. Methods and results In a single‐centre, open‐label evaluation, patients with NYHA class III HF, EF <40%, optimized medical therapy, and ineligible for cardiac resynchronization received BAT for 6 months. Efficacy was assessed with serial measurement of muscle sympathetic nerve activity (MSNA) and clinical measures of quality of life and functional capacity. Eleven patients participated in the trial. MSNA was reduced over 6 months from 45.1 ± 7.7 to 31.3 ± 8.3 bursts/min and from 67.6 ± 12.7 to 45.1 ± 11.6 bursts/100 heartbeats, decreases of 31% and 33%, respectively (P < 0.01). Concomitant improvements occurred in baroreflex sensitivity, EF, NYHA class, quality of life and 6 min hall walk (6MHW) distance (P ≤ 0.05 each). On an observational basis, hospitalization and emergency department visits for worsening HF were markedly reduced. One complication, perioperative anaemia requiring transfusion, occurred during the study. Conclusion BAT was safe and provided chronic improvement in MSNA and clinical variables. Based on present understanding of HF pathophysiology, these results suggest that BAT may improve outcome in HF by modulating autonomic balance. Prospective, randomized trials to test the hypothesis are warranted.